PERBEDAAN HITUNG JUMLAH LEUKOSIT SEGERA DAN DISIMPAN SELAMA 6 JAM - Aristoteles; Nanik Puspitasari (IKesT Muhammadiyah Palembang, 2023)
Introduction: Leukocytes are blood cellscontaining nuclei, orso-called white blood cells. Leukocytes have a role in the cellular and humoral defense of organisms against foreign substances. Some types of leukocytes or white blood cells are present in the blood. Leukocytes are generally divided into granuocytes (which have special granules) andagranulocytes (which do not have special granules). Granulocytes consist of neutrophils, eosinophils, and basophils. Agranulocytes consist of lymphocytes and monocytes. Leukocyte count examination is a routine blood test conducted in the clinical laboratory because of the frequent request for a test to calculate the number of leukocytes. Calculate the number of leukocytes not only determinethe number ofleukocyte cells, but can also be any type of leukocyte cells. Objectives: The purpose of this study is to determine the difference in the number of leucocytes immediately and stored for 6 hours.Methods: This research method usescross sectional, this sample was taken from studentslevel 1 and 4Medical Laboratory Technologyof Health Sciences and Technology Muhammadiyah Palembang. Result: The results of this study obtained an averagecount of the number of leukocytes immediately is 6.3667 cells/μl, while the average count of the number of leukocytes stored for 6 hours is6.4667 cells/μl. Result: The results of T-test statistics showed a significant value (0,477) was higher than the alpha value of 0.05 or ρ>ɑthen Ho, receivedwhich means there is no difference in calculating the number of leukocytes immediately and stored for 6 hours. Conclusion: The conclusion of this study is that there is no difference in calculating the number of leukocytes immediately and disinced for 6 hours.